Herding behaviour in cryptocurrency and emerging financial markets - Maurice Omane-Adjepong; Imhotep Paul Alagidede; Anna Gustav Lyimo; George Tweneboah (Cogent Economics & Finance, 2021)
The letter examines herding in the most liquid cryptocurrency markets relative to traditional financial markets of 10 emerging economies within the G20. Our results reference significant symmetric crowd and imitation trading, which are dependent on time. Additionally, we report asymmetric herd behaviour in the cryptocurrency and stock markets, indicative that traders of these markets react collectively to extreme return movement with implied high risk and consequences for market informational efficiency.
Keywords: C22; G10; 330; g20; cryptocurrency; emerging markets; Herding